The consumption-oriented capital asset pricing model in the Nigerian Stock Exchange - Abidemi C. Adegboye (CBN Journal of Applied Statistics, 2017)
In this study, the Consumption-oriented Capital Asset Pricing Model (CCAPM) is tested for Nigeria by considering returns on investments in the Nigerian Stock Exchange market and other financial assets for the period 1993: Q1 to 2016:Q4. Three tests are conducted. The first test examines forecast performance of excess returns for the selected portfolios in predicting future consumption; the second test estimates the consumption betas for the set of assets using two alternative formulations of the CCAPM; and the third test included consumption growth variable in a multifactor risk analysis to compare with the basic CAPM formulations. The empirical results indicates that while stock returns do not predict future consumption decisions well, both Treasury Bill rates and dividend yield performed well in predicting consumption behaviour. For the consumption beta estimates, CCAPM is found to only be relevant for few portfolios in the stock market, with negative betas for the entire market. Betas for Treasury bill rates and dividend yields however suggest that the assets form strong basis for both current and future consumption decisions. The results also show that the consumption growth factor does not have any significant risk premium for the categories of assets.
Keywords: E44; G12; G11; 330; CCAPM; Consumption Growth; Dividend Yield; Excess Returns; NSE; Treasury Bill Rate